Dynamics of free radicals processes in rat blood with partially blocked thyroid gland by stable iodine - Yu. P. Grynevych; A. I. Lypska; I. P. Drozd; S. V. Teletska (Ядерна фізика та енергетика)
Free radicals' processes in blood of male rats Wistar, induced by Н2О2 chemiluminescence for single oral ingestion of 131І in organism at 65.9 kBq per animal in conditions of partially blocked thyroid gland with 127I, were studied. The introduction of radioactive iodine, as well as partial blocking of thyroid gland by iodine, do not influence significantly on changing of prooxidant-antioxidant homeostasis and oxidative correlation lipid peroxidation in blood for chemiluminescence reaction (sum light emission, the final intensity of the light emission, maximum intensity of the first flash light emission, velocity formation of free radicals, time to reach maximum values intensity of the first flash light emission). There were no significant changes in catalase activities in the experimental rat blood from those in the control group rats.